Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jum.15591
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Lateral Abdominal Wall Botulinum Toxin Injection Before Ventral Hernia Repair

Abstract: Preoperative ultrasound‐guided lateral abdominal wall botulinum toxin injection is a promising method for improving patient outcomes and reducing recurrence rates after ventral hernia repair. A review of the literature demonstrates variability in the procedural technique, without current standardization of protocols. As radiologists may be increasingly asked to perform ultrasound‐guided botulinum toxin injections of the lateral abdominal wall, familiarity with the procedure and current literature is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…A statistically significant decrease in the size of the transverse hernia defect and loss of domain following the Botox injection supported the study's findings that Botox injection was beneficial in easing muscular tension and attaining primary fascial closure. The study's results are in line with other research that showed how well Botox injections could help patients with complicated abdominal wall hernias by easing muscular tension and promoting primary fascial closure [20,21]. Following the Botox injection, there was a statistically significant decrease in the size of the transverse hernia defect (p 0.001).…”
Section: Discussionsupporting
confidence: 88%
“…A statistically significant decrease in the size of the transverse hernia defect and loss of domain following the Botox injection supported the study's findings that Botox injection was beneficial in easing muscular tension and attaining primary fascial closure. The study's results are in line with other research that showed how well Botox injections could help patients with complicated abdominal wall hernias by easing muscular tension and promoting primary fascial closure [20,21]. Following the Botox injection, there was a statistically significant decrease in the size of the transverse hernia defect (p 0.001).…”
Section: Discussionsupporting
confidence: 88%